2016
DOI: 10.1007/s40894-016-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Disabilities

Abstract: Adolescents with disabilities face many challenges common to their typically developing peers. However, the ways that they resolve them may differ. The focus of this narrative overview was to summarize results from the disabilities in adolescence literature, highlight common research directions, evaluate the overall big picture of this literature, and draw conclusions based on general interpretations. Evidence suggests that the literature in this field of study is lacking. Suggestions for improvement include i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 109 publications
2
40
1
1
Order By: Relevance
“…Although the evidence base is fledgling (Jones et al 2018a;Groce and Kett 2014), adolescents with disabilities have been found to be disproportionately prone to challengesin part because 'societal and cultural views of disability can take on additional meaning during the adolescent years', when young people become increasingly aware of individual differences and young people with disabilities are forced to more directly confront and balance their needs for autonomy and support (Maxey and Beckert (2017). However, even in the Global North there has been little attempt to methodically investigate the nexus of adolescence and disabilityan oversight which has left many of the barriers to successful transitions to adulthood opaque and unaddressed (ibid.)…”
Section: Focusing On Adolescencementioning
confidence: 99%
“…Although the evidence base is fledgling (Jones et al 2018a;Groce and Kett 2014), adolescents with disabilities have been found to be disproportionately prone to challengesin part because 'societal and cultural views of disability can take on additional meaning during the adolescent years', when young people become increasingly aware of individual differences and young people with disabilities are forced to more directly confront and balance their needs for autonomy and support (Maxey and Beckert (2017). However, even in the Global North there has been little attempt to methodically investigate the nexus of adolescence and disabilityan oversight which has left many of the barriers to successful transitions to adulthood opaque and unaddressed (ibid.)…”
Section: Focusing On Adolescencementioning
confidence: 99%
“…Other factors are changing external circumstances, such as transition to the next educational stage, and the need to adapt to the new requirements and the new peer environment [22,23,56,57]. Maxey and Beckert [11] stress the importance of relationships with parents, siblings, and friends; the impact of school; access to new technologies; and involvement in extracurricular activities, as factors that play a role in the psychosocial functioning of adolescents and affect their locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…Entering the period of adolescence together, they take on various biological, cognitive, and social challenges that naturally come with this period of life. Although the literature on how young people with various types of disabilities experience the period of adolescence is still scarce [11], the key characteristics of their functioning are readily outlined.…”
Section: Education Of Students With Disabilities and Their Nondisablementioning
confidence: 99%
“…Transition is often associated with movement from a more shielded environment to a more self-directed environment. It is characterised by the ability to make decisions and to take care of oneself [7]. Transition also includes many adjustments that have to occur in life.…”
Section: Transition As a Conceptmentioning
confidence: 99%
“…Transition of adolescents with ID into adulthood has been a concern not just for researchers but for national governments as well. Most governments encourage the principle of inclusion in schools and employment [7]. In some instances, policies have been developed that encourage inclusion and provide more opportunities for adolescents with ID aiming at maximising their interaction with the wider community.…”
Section: Governmental Interventionsmentioning
confidence: 99%